A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic - Bekker, Eugeniya I.; Kotov, Alexey A. (Zootaxa, 2016)
Our study is aimed at a taxonomic revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera: Eurycercidae) in the Holarctic based on the morphology of parthenogenetic females. Three species were revealed and described: (1) E. glacialis Lilljeborg, 1887 which is relatively widely distributed in the north portion of Atlantic and Pacific regions; (2) E. nigracanthus Hann, 1990 which is apparently present in Labrador and Newfoundland, Cape Breton Island and Nova Scotia and (3) Eurycercus chernovi sp. nov. from Taimyr Peninsula in Siberia, Russia. Main differences of the latter taxon from other species are: (1) more proximal position of sensory seta on the antenna I and (2) surface of cuticle of major head pore forms a low projection in middle. A revision of this subgenus in Arctic Siberia and Canada needs to be continued.